2018
DOI: 10.1213/ane.0000000000003406
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Perioperative Cardiovascular and Respiratory Adverse Events in Pediatric Patients With Congenital Heart Disease Undergoing Noncardiac Procedures

Abstract: Intraoperative cardiovascular events and respiratory events in patients with CHD were relatively common. While cardiovascular events were highly associated with cardiovascular status, respiratory events were not associated with cardiovascular status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
2
15
0
3
Order By: Relevance
“…Non-cardiac surgery included otolaryngology, maxillofacial, gastroenterology and general surgical procedures. The more severe the CHD, the higher the risks of reintubation and mortality [ 30 ].…”
Section: Preoperative Risk Assessment and Stratificationmentioning
confidence: 99%
“…Non-cardiac surgery included otolaryngology, maxillofacial, gastroenterology and general surgical procedures. The more severe the CHD, the higher the risks of reintubation and mortality [ 30 ].…”
Section: Preoperative Risk Assessment and Stratificationmentioning
confidence: 99%
“…4 Similarly, in a large single-center cohort study, Lee et al demonstrated an 11.5% incidence of cardiovascular events and a 4.7% incidence of respiratory complications perioperatively. 5 Hence, proper diagnosis and anticipation of the challenges posed by airway abnormalities in CHD patients is crucial in reducing perioperative morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory events were associated with an ASA status of 4 or higher, and otolaryngology, gastrointestinal, general surgery, and maxillofacial procedures. They found that the incidence of cardiac events was higher than respiratory events, and though cardiovascular events were associated with cardiovascular status, respiratory events were not [29]. Institutions should consider the need for and availability of specialty trained pediatric cardiac anesthesiologists for complex congenital heart disease patients.…”
Section: Cardiovascular Eventsmentioning
confidence: 99%